2019
DOI: 10.3855/jidc.10479
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and practice for hepatitis B infection in Southeast Asia: a cross-sectional study

Abstract: Introduction: The prevalence of hepatitis B virus (HBV) infection in Southeast Asia is high. Awareness and early detection are essential for timely prevention and treatment. Methodology: We examined the awareness of, knowledge about, practices and views on treatment for HBV infection in Southeast Asia. A cross-sectional survey was conducted from December 2016 to February 2017 among individuals from six nations in Southeast Asia-Myanmar, Thailand, Vietnam, Cambodia, the Philippines, and Singapore. The study pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Approximately one‐quarter had misunderstood that hepatitis is transmissible by mosquito bites. These misconceptions of the transmission modes of viral hepatitis may be irrespective of a country/territory's liver index, wherein, similar findings were also observed in some community‐based surveys across Asia 31,32,41 . A survey in India showed that only 3 in 10 people were knowledgeable about the different modes of transmission of HBV 32,41 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Approximately one‐quarter had misunderstood that hepatitis is transmissible by mosquito bites. These misconceptions of the transmission modes of viral hepatitis may be irrespective of a country/territory's liver index, wherein, similar findings were also observed in some community‐based surveys across Asia 31,32,41 . A survey in India showed that only 3 in 10 people were knowledgeable about the different modes of transmission of HBV 32,41 .…”
Section: Discussionsupporting
confidence: 64%
“…These misconceptions of the transmission modes of viral hepatitis may be irrespective of a country/territory's liver index, wherein, similar findings were also observed in some community-based surveys across Asia. 31,32,41 A survey in India showed that only 3 in 10 people were knowledgeable about the different modes of transmission of HBV. 32,41 In Pakistan, a study also reported that majority of the study population had expressed confusions regarding the transmission mode and vaccination protocols of HBV and HCV, which were corrected during an awareness campaign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were not unique to Singapore and were also commonly observed in community studies conducted across Southeast Asia. 40,41 Like HBV, HCV is also a blood-borne disease; however, there is currently no available vaccine to prevent HCV, which remains a common misperception globally. 42 Instead, the recent development of oral DAA treatment regimens for HCV resulted in a successful initial cure rate of up to 99% with minimal side effects, prompting a step closer towards WHO's viral HCV eradication goal.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were not unique to Singapore and were also commonly observed in community studies conducted across Southeast Asia. 40 , 41 …”
Section: Discussionmentioning
confidence: 99%